Sharing Economy: A Systematic Literature Review - Agarwal, Nivedita; Steinmetz, Robert (Emerging Issues and Trends in Innovation and Technology Management, 2021)
The paper employs a Systematic Literature R eview approach to investigate the evolution of the term sharing economy and to identify the future potential research pathways. Analysis of the key publications reveals high emphasis on conceptual studies and qualitative methodologies within the academic literature on sharing economy. This study classifies the literature into five main categories of sustainability, participant behavior, regulatory framework, business models and conceptual studies. Highlighting the research gaps, this study also calls for further research on understanding the roles of other stakeholders such as government and municipalities, analyzing the influence of cultural background and exploring the possibilities for B2B businesses to engage in sharing economy.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Access-based consumption; Collaborative consumption; Peer-to-peer sharing; Sharing economy; Sustainability